PENGEMBANGAN BAHAN AJAR BERBASIS WEB DENGAN MENGGUNAKAN ADOBE DREAMWEAVER CS6 PADA MATA KULIAH EVALUASI PROSES DAN HASIL PEMBELAJARAN SEMESTER V PROGRAM STUDI TEKNOLOGI PENDIDIKAN UNIVERSITAS BATURAJA - Muda, Yelmi ; Ningsih , Sulia (Universitas Bina Darma, 2018)
This study aims to develop and produce website based teaching materials using Adobe Dreamweaver CS6 in the evaluation of learning process and achievement course at fifth semester of Educational Technology Study Program at Baturaja University. This study was conducted using Bambang Warsita’s Research and Development model design. The results showed that the design, media, and material expert evaluations were at good category (84.27%, 83.6% ,and 81.4%). Meanwhile, individual evaluation result was 82.52% (good), small group evaluation was 82.99% (good), and field trial result was 83.48% (good). In addition, students also commented that website based teaching materials are good, varied, interesting and fun. From the results of the data analysis, it can be concluded that website based teaching materials using Adobe Dreamweaver CS6 are good and can be used in the learning process. Keywords: Adobe Dreamweaver CS6, Web-based teaching materials, process evaluation and learning outcomes